Investigating the Cu-based catalysts for char catalytic hydrogasification and its recovery. (15th June 2021) - Sun, Hao; Wang, Jinting; Bi, Jicheng; Zhang, Rong; Qu, Xuan; Zhang, Jinli; Zhang, Jianshu
Graphical abstract: Clean, efficient and circular development concept. Highlights: Methane yield of 60.6% was achieved with 5Cu-1Ca in 800 °C and 2 MPa H2 . The interaction between calcium and sulfur mainly occurred at the initial stage of reaction. Cu-Ca catalyst inhibit the graphitization and increase the active sites for char. The Cu leaching rate reached 94.7% in NH3 -NH4 HCO3 system. Removing sulfur from the recovered liquid could promote the activity and cycle life of the catalyst. Abstract: Cobalt and nickel exhibit excellent catalytic properties in coal hydrogenation, which makes these metals potentially attractive as coal hydrogasification catalysts. However, cobalt and nickel are quite expensive. Herein, a relatively cheap copper catalysts are investigated for coal/char catalytic hydrogasification in a pressurized fixed-bed reactor. And copper is recovered from the residue by pressurized oxidizing ammonia leaching. The 5Cu-1Ca catalyst shows a higher activity on methane yield of 60.6% in char catalytic hydrogasification at 800 °C and 2 MPa H2 . Calcium plays a significant role to inhibit sulfur poisoning of copper catalysts by capturing the sulfur to form calcium sulfide. And the formation of calcium sulfide mainly takes place during the initial stage of the reaction. The interaction between copper and carbon expedites the cleavage of C–C bonds in char. Cu-Ca catalysts not only inhibit the graphitization but also increase the active sites for char. Further, pressurized oxidizing ammonia leaching is employed to recover copper from the residue, and the Cu leaching rate reaches 94.7% in NH3 -NH4 HCO3 system. Finally, recycling experiments prove that removing sulfur from the filtrate can improve catalytic activity and cycle life of the catalyst.